MENINGKATKAN PEMAHAMAN SHALAT: EFEKTIVITAS METODE DEMONSTRASI PADA SISWA KELAS II SD 'AISYIYAH 1 MATARAM - Mardiyah Hayati; Dewi Urifah; Niswatun Hasanah; Yuliananingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the effectiveness of implementing the demonstration method in teaching Islamic jurisprudence, specifically focusing on the topic of prayer, at SD ‘Aisyiyah 1 Mataram. In the context of a school with a rigorous Islamic curriculum, the demonstration method is expected to provide a clear depiction of prayer practices and enhance students' practical skills. This research employs a descriptive qualitative approach, utilizing data collection methods such as interviews, observations, and documentation, with data analysis conducted through qualitative descriptive techniques. The findings reveal that the demonstration method is effective in helping students understand and practice the movements of prayer. Key factors contributing to the method’s effectiveness include thorough preparation, the provision of appropriate teaching aids, and the strategic placement of the demonstration area. However, certain limitations such as the availability of tools and classroom space need to be addressed to optimize learning outcomes. Overall, this study underscores that the demonstration method has significant potential to improve students’ understanding and practice of prayer when applied with proper planning, innovation, and ongoing evaluation.